Association Between Residence And Disease Incidences In The Dr. Soetomo Hospital Psychiatric Clinic - Firda Fauziah Hidayat; Khairina Khairina; Budi Utomo (Faculty of Medicine, Universitas Airlangga, 2021)
Background; The increasing mental disorders prevalence adds countries’ burdens. One of the mental disorder’s risks is residence. There is no research about the relationship between residence and ten most psychiatric diseases in Surabaya. Objective; This research aims to study the relationship between residence and ten most diseases in Dr. Soetomo hospital psychiatric clinic. Methods; This research method using observational-analytic design with a cross-sectional approach in Dr. Soetomo hospital psychiatric clinic. Data were taken from medical records based on inclusion and exclusion criteria. The research used a chi-square test with 95%CI. Results: The dominant districts where research subjects lived were education-related psychiatric examinations in Semampir, paranoid schizophrenia in Sawahan, mental disorders due to brain damage in Sawahan, moderate depressive episodes in Gubeng, MMR in Kenjeran, activity and behavior disorders in Sawahan, hebefrenic schizophrenia in Tambaksari, family-related psychiatric examinations in Tambaksari, atypical autism in Sukomanunggal and Semampir, MADD in Tambaksari. Distribution of patients’ residence based on five regions of Surabaya was East Surabaya as the dominant residence of paranoid schizophrenia, moderate depressive episodes, hebefrenic schizophrenia, atypical autism, MADD; North Surabaya as the dominaNt residence of education-related psychiatric examinations, MMR; South Surabaya as the dominant residence of paranoid schizophrenia, mental disorders due to brain damage, activity and behavior disorders, family-related psychiatric examinations. Chi-square test showed a significant relationship between residence and ten most diseases. Conclusion; There is a significant (goodness of fit) relationship between residence and ten most diseases in Dr. Soetomo hospital psychiatric clinic. Keywords: Mental disorders, Residence, Surabaya City